PENGGUNAAN DISFEMISME OLEH PEMBENCI (HATERS) DALAM INSTAGRAM PADA AKUN ARTIS AYU TING TING - Hermawan, Dina Hartanti; Faizah, Hasnah; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study describes the use of dysfism by haters in instagram on artist Ayu Ting Ting's account. The purpose of this research is to describe the form and function of dysfismism used by haters in instagram on artist account of Ayu Ting Ting. This type of research is qualitative research with descriptive method, it means to analyze and describe data descriptively. This research data collection using documentation technique. Based on data analysis that has been done, found 112 form of dysemism with division of (a) word form 59 data with details of base word amounted to 33 data, said berimbuhan 23 data, repeat 1 data and compound word 2 data. (b) the phrase form 41 data. (c) an expression or idiom form of 12 data with full idiomatic details of 3 data and idiom of some 9 data. The dysfemism function used by the haters in the instagram of Ayu Ting Ting's artist account is eight functions, with details (a) as an intermediary to declare taboos or indecent items totaling 7 data. (b) as a dislike, hate, and disrespect of 22 data. (c) as an intermediary to express anger or aggravation amounted to 19 data. (d) as a negative depiction of something amounting to 1 data. (e) as a means of humiliating and mocking a total of 17 data. (f) as a means to criticize a total of 20 data. (g) as a means of exaggeration and cursing of 22 data. (h) as indicator of low value of 4 data.Keywords: dysphemism, haters, instagram, ayu ting ting.